MULTIFACETED ROLE OF INDIGENOUS CHICKEN IN INDIA: A REVIEW - R. Islam; S. Islam; I. U. Sheikh; M. Rahman (Indian Journal of Veterinary and Animal Sciences Research, 2025)
This article attempts to review the role of indigenous chicken in rural India. Indigenous chicken farming is an age-old practice and an important tool to reduce poverty among the most under-privileged section of the Indian society particularly the rural tribes. It results in socio-economic development, nutritional and livelihood security, empowerment of women etc. among rural people. The surplus income earned from poultry rearing was used on education (33 %) and food (30 %). Majority (49.5 %) of the respondents reared indigenous chicken to meet petty expenses in Assam. Majority (67.5 %) of the indigenous chicken farmers were women, hence decisions for hatching, selling of surplus chicks eggs etc. were made by the women and they may be empowered greatly through improvement of their skills. It is an eco-friendly approach, where birds can exhibit their normal and natural behavior Birds are kept mostly on scavenging system, where they acquire their feeds through natural foraging, kitchen wastes etc. Rural poultry farming has been responsible to produce 40 per cent meat and 44 per cent egg requirement in India. Chicken eggs and meat are the only cheapest and best sources of protein, vitamin and minerals with high biological value for rural poor and marginal sections of people. In many parts of India, indigenous communities particularly tribal people not only consume chicken and eggs but also use them extensively in indigenous rituals performed to satiate gods, spirits of ancestors and nature, ward-off demons and evil spirits, get rid of bad luck, sacrificed during initiation of agriculture activities and new business, weddings, birth and death ceremonies. The additional income earned from indigenous chicken farming was used to improve their socio-economy.